2016
DOI: 10.1007/s12024-016-9810-0
|View full text |Cite
|
Sign up to set email alerts
|

Forensic postmortem computed tomography: volumetric measurement of the heart and liver

Abstract: Noninvasive in situ PMCT methods for organ measuring, as performed in this study, are not useful tools in forensic pathology. The best method to estimate organ volume is a CT-scan of the eviscerated organ. PMCT-determined CTR seems to be useless for ascertaining cardiomegaly, as it neither correlated with the ex vivo heart volume nor with the HWR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A formula of adjusted CTR-based score could help to predict "cardiomegaly" at postmortem computed tomography (PMCT) [15]. Several studies showed that postmortem radiological measurements of wall thicknesses including PMCT and postmortem magnetic resonance (PMMR) differ from corresponding autopsy measurements [16][17][18][19][20]. It was shown that LV wall thickness was significantly higher on PMCT compared to PMMR and that LV anterior wall thickness was significantly higher on PMMR than at autopsy [17].…”
Section: Interstitial Fibrosismentioning
confidence: 99%
“…A formula of adjusted CTR-based score could help to predict "cardiomegaly" at postmortem computed tomography (PMCT) [15]. Several studies showed that postmortem radiological measurements of wall thicknesses including PMCT and postmortem magnetic resonance (PMMR) differ from corresponding autopsy measurements [16][17][18][19][20]. It was shown that LV wall thickness was significantly higher on PMCT compared to PMMR and that LV anterior wall thickness was significantly higher on PMMR than at autopsy [17].…”
Section: Interstitial Fibrosismentioning
confidence: 99%
“…One person conducted the manual segmentation and this is a limitation. However, CTR measurements and volumetric organ measurements have shown high interrater agreements [2,3,6,30,31]. Secondly, not all possible causes of death were assessed and hypothermia group was very small so the two hypothermia cases which fulfilled the inclusion criteria had to be excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, they suffer from several disadvantages at the moment, which is why they cannot substitute traditional autopsy in all cases. Specifically, virtual autopsy cannot provide information about the odour and texture of organs, as well as volume measurements, which may be of great importance in diagnostics (Bolliger & Thali, 2015;Jakobsen et al 2016).…”
Section: Discussionmentioning
confidence: 99%